1996
DOI: 10.1007/bf00176700
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of electroneuronography with facial nerve latency testing for prognostic accuracy in patients with Bell's palsy

Abstract: The purpose of this study was to evaluate the ability of electroneuronography (ENOG), also called evoked electromyography (EEMG), and facial nerve latency testing (FNLT) to assess the prognosis of facial nerve palsy, using the House-Brackmann facial nerve grading system as criterion. From 1988 to 1994 these tests were employed at the ORL Clinic of the University of Ioannina in 250 patients with idiopathic facial nerve palsy. The ENOG test results indicated that when the amplitude of the compound muscle action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The neurophysiological status of the facial nerve and the degree of nerve injury were determined by two quantitative electrodiagnostic tests (electroneuronography [2,4,5] and the facial nerve latency test [2,8,10]) and one qualitative test (the maximum nerve stimulation test [1,9]). …”
Section: Methodsmentioning
confidence: 99%
“…The neurophysiological status of the facial nerve and the degree of nerve injury were determined by two quantitative electrodiagnostic tests (electroneuronography [2,4,5] and the facial nerve latency test [2,8,10]) and one qualitative test (the maximum nerve stimulation test [1,9]). …”
Section: Methodsmentioning
confidence: 99%
“…Similar analyses were performed using the FNLT and MUAP groupings of Danielides et al 14,15 The results are shown in Table 4. There were no significant differences between surgical approaches in FNLT groupings for any of the four time periods (P > 0.05 for each).…”
Section: Resultsmentioning
confidence: 97%
“…This finding is supported by the studies reported by Danielides et al, in which the authors showed a correlation between the latency time and MUAP and the prognosis of the facial nerve disorder. 14,15 Based on the results of the present study, postoperative facial nerve injury is a multifactorial complication that is transient in nature and does not depend on the surgical approach alone. Other contributing factors include the type of surgery, the surgical difficulties encountered, the duration of surgery, and previous surgery to the joint.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the past, results were used to decide who might be a candidate for controversial and now out-of-vogue procedures such as intracanicular decompression. [1][2][3][4][5] The natural history of Bell's palsy is that 50-60% of patients will recover in three weeks 1 and 80-90% have normal or near-normal recovery by six months. 6 If the maximal deficit is paresis rather than palsy, nearly all (>95%) patients will achieve a full recovery three to eight weeks after onset.…”
mentioning
confidence: 99%